Comparative study of consumer satisfaction offline shopping and online using e-commerce Tokopedia to loyalty during the Covid-19 pandemic - Irene Vikining Astuty R; Kiromim Baroroh (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study aims to determine the comparison of consumer satisfaction shopping offline and online using e-commerce. Tokopedia towards covid-19 pandemic. The method used in this research is comparative descriptive using a quantitative and survey approach. The total population in this study was 280 people with a total sample of 165 respondents. The technique used was probability sampling with purposive sampling. This data collection uses observation and questionnaires. The data collected through a questionnaire was then processed using the SPSS 15.0 program. The results obtained show that the variable of consumer satisfaction when shopping online and offline has a significant difference so that it has an impact on consumer loyalty online and offline. The loyalty experienced by consumers shopping online tends to be less than the loyalty to shop directly. Where when consumers make transactions directly, consumers tend to be more daring in making decisions in shopping because consumers are able to choose, see and touch directly the goods or products to be purchased so that they will make their own commitment to the product, brand and store.